Biopharmaceuticals - Yeh, Ming-Kung; Chen, Yuan-Chuan (IntechOpen, 2018)
Biopharmaceuticals are derived from biological sources, either live organisms or their active components; nowadays, they are mainly produced by biotechnologies. Biopharmaceuticals are extensively used in the treatment of various diseases such as cardiovascular, metabolic, neurological diseases, cancer, and others for which there are no available therapeutic methods. With the advance of science, biopharmaceuticals have revolutionized the treatment, prevention, and diagnosis of many patients with disabling and life-threatening diseases. Innovative biopharmaceuticals definitely improve the life quality of patients and enhance the effectiveness of the healthcare system. This book encompasses the discovery, production, application, and regulation of biopharmaceuticals to demonstrate their research achievement, prospects, and challenges. We expect the significance of biopharmaceuticals to be revealed and emphasized by this book.